Trans-synaptic interactions of ionotropic glutamate receptors. (February 2021) - Fossati, Matteo; Charrier, Cécile
Highlights: Most iGluRs engage in extracellular and trans -synaptic interactions. iGluR trans -synaptic interactions specify the formation of synaptic connections. GluD1 trans -synaptic signaling controls inhibitory circuit specificity in the cortex. iGluR trans -synaptic interactions mediate input-specific trapping at synapses. Abstract : Trans -synaptic interactions organize the multiple steps of synaptic development and are critical to generate fully functional neuronal circuits. While trans -synaptic interactions are primarily mediated by cell adhesion molecules (CAMs), some directly involve ionotropic glutamate receptors (iGluRs). Here, we review the expanding extracellular and trans -synaptic proteome of iGluRs. We discuss the role of these molecular networks in specifying the formation of excitatory and inhibitory circuits and in the input-specific recruitment of iGluRs at synapses in various cell types and brain regions. We also shed light on human-specific mutations affecting iGluR-mediated trans -synaptic interactions that may provide unique features to the human brain and contribute to its susceptibility to neurodevelopmental disorders. Together, these data support a view in which iGluR function goes far beyond fast excitatory synaptic transmission by shaping the wiring and the functional properties of neural circuits.